New laser polarization line at the ISOLDE facility. (30th June 2017) - Kowalska, M; Aschenbrenner, P; Baranowski, M; Bissell, M L; Gins, W; Harding, R D; Heylen, H; Neyens, G; Pallada, S; Severijns, N; Velten, Ph; Walczak, M; et al.
Abstract: Following a growing interest in spin-polarized beams of radioactive ions, a new laser spin-polarization setup has been installed at the ISOLDE facility at CERN. The setup is located at the VITO beamline which aims to bring together several experimental techniques using polarized ions allowing for studies in nuclear physics, fundamental interactions, material and life sciences. Intensive design work, which took place in 2016, allowed the installation of the first stage of the polarization line. With this experimental setup, the ion beam can be neutralized, polarized and implanted into a solid sample inside an electromagnet which also hosts β -detectors, where the degree of nuclear spin polarization can be measured. In autumn 2016 the setup was commissioned using short-lived 26 Na and 28 Na beams which were polarized in the D2 line from their atomic ground state. The previously observed degrees of β asymmetry were reproduced and thus the beamline is now ready for the first physics experiments with spin-polarized radioactive beams.